Legg–Calve–Perthes Disease - N. Yu. Krutikova; A. G. Vinogradova (Вопросы современной педиатрии, 2015)
Legg–Calve–Perthes disease is a form of femur and hip joint pathology that belongs to the osteochondropathy group. The disease is caused by disorders of blood circulation and nutrition of articular cartilage leading to necrosis of the femoral head. The etiology of thedisease has not been clearly established yet. The destruction of the cartilage and bone tissue of the femoral head occurs gradually and is most often diagnosed in children over 5 years old. Since the identification of groups at risk for this disease is difficult, patients often seek help at the height of clinical manifestations, when the bone destruction is quite significant. Late treatment leads to the development of resistant strains of the femoral head, increasing the duration of treatment and reducing the quality of life of patients. The article presents the data of contemporary literature on the basic concepts of the pathology, its epidemiological and clinical features, and diagnostic and therapeutic measures.